This preview shows page 1. Sign up to view the full content.
Unformatted text preview: (z**3)'5 + )0x * lS z) ?3 U+\x 3r*5) * (zx + (-( 9 ^t ILx.-g tzx (Zn-]) 8x3 - lzxa - l4 xl * 36x Zx-3J u T(u-3) + lt x*D (d) (" - 3a)Qa - 7r) = K'.y _ 7r. - 0). +@y) G ?x, =}I:]xL- (f +zlrl = I A \ :/Zxr -1x=+ f Yrr-15 (c) (2r- 3), = [fx-3] [ tx4)( =(qf-lzx-rq)(.z^-3J...
View Full Document
This note was uploaded on 12/27/2011 for the course MAC 1105 taught by Professor Picklesimer during the Fall '10 term at University of Florida.
- Fall '10